CETP (Cholesteryl Ester Transfer Protein) Concentration: A Genome-Wide Association Study Followed by Mendelian Randomization on Coronary Artery Disease. (May 2018) - Blauw, Lisanne L.; Li-Gao, Ruifang; Noordam, Raymond; de Mutsert, Renée; Trompet, Stella; Berbée, Jimmy F.P.; Wang, Yanan; van Klinken, Jan B.; Christen, Tim; van Heemst, Diana; Mook-Kanamori, Dennis O.; Rosendaal, Frits R.; et al.
Abstract : Background: We aimed to identify independent genetic determinants of circulating CETP (cholesteryl ester transfer protein) to assess causal effects of variation in CETP concentration on circulating lipid concentrations and cardiovascular disease risk. Methods: A genome-wide association discovery and replication study on serum CETP concentration were embedded in the NEO study (Netherlands Epidemiology of Obesity). Based on the independent identified variants, Mendelian randomization was conducted on serum lipids (NEO study) and coronary artery disease (CAD; CARDIoGRAMplusC4D consortium). RESULTS: In the discovery analysis (n=4248), we identified 3 independent variants ( P <5×10 −8 ) that determine CETP concentration. These single-nucleotide polymorphisms were mapped to CETP and replicated in a separate subpopulation (n=1458). Per-allele increase (SE) in serum CETP was 0.32 (0.02) µg/mL for rs247616-C, 0.35 (0.02) µg/mL for rs12720922-A, and 0.12 (0.02) µg/mL for rs1968905-G. Combined, these 3 variants explained 16.4% of the total variation in CETP concentration. One microgram per milliliter increase in genetically determined CETP concentration strongly decreased high-density lipoprotein cholesterol (−0.23 mmol/L; 95% confidence interval, −0.26 to −0.20), moderately increased low-density lipoprotein cholesterol (0.08 mmol/L; 95% confidence interval, 0.00–0.16), and was associated with an odds ratio of 1.08 (95% confidence interval, 0.94–1.23) for CAD risk. Conclusions: This is the first genome-wide association study identifying independent variants that largely determine CETP concentration. Although high-density lipoprotein cholesterol is not a causal risk factor for CAD, it has been unequivocally demonstrated that low-density lipoprotein cholesterol lowering is proportionally associated with a lower CAD risk. Therefore, the results of our study are fully consistent with the notion that CETP concentration is causally associated with CAD through low-density lipoprotein cholesterol. Abstract : Supplemental Digital Content is available in the text.